2020
DOI: 10.1021/acs.orglett.0c00598
|View full text |Cite
|
Sign up to set email alerts
|

C–H Amination of Arenes with Hydroxylamine

Abstract: This Letter describes the development of a Ti IIImediated reaction for the C−H amination of arenes with hydroxylamine. This reaction is applied to a variety of electronrich (hetero)arene substrates, including a series of natural products and pharmaceuticals. It offers the advantages of mild conditions (room temperature), fast reaction rates (<30 min), compatibility with ambient moisture and air, scalability, and the use of inexpensive commercial reagents.A niline derivatives (ArNH 2 ) appear in a wide variety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 39 publications
(40 reference statements)
1
20
0
1
Order By: Relevance
“…Toward this endeavour our group and others have been working on iron catalyzed aminofunctionalization of alkenes [76–82] using hydroxylamine derived reagents. Additionally, we and others reported aromatic C−H amination reactions [83–87] through the use of similar reagents. The versatile reactivity of these iron catalyzed reactions of hydroxylamine derivatives in hydrocarbon functionalization reactions prompted us to investigate their reactivity in heteroatom amination reactions.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Toward this endeavour our group and others have been working on iron catalyzed aminofunctionalization of alkenes [76–82] using hydroxylamine derived reagents. Additionally, we and others reported aromatic C−H amination reactions [83–87] through the use of similar reagents. The versatile reactivity of these iron catalyzed reactions of hydroxylamine derivatives in hydrocarbon functionalization reactions prompted us to investigate their reactivity in heteroatom amination reactions.…”
Section: Introductionmentioning
confidence: 79%
“…Widely studied iron-based enzymes have recently inspired ar enewed interest in developing simple,h omogeneous iron complexes for the oxidation and amination of organic substrates. [75] Toward this endeavour our group and others have been working on iron catalyzed aminofunctionalization of alkenes [76][77][78][79][80][81][82] using hydroxylamine derived reagents.A dditionally,w ea nd others reported aromatic CÀHa mination reactions [83][84][85][86][87] through the use of similar reagents.T he versatile reactivity of these iron catalyzed reactions of hydroxylamine derivatives in hydrocarbon functionalization reactions prompted us to investigate their reactivity in heteroatom amination reactions.N otably,t he Bolm group has elegantly harnessed our previously reported iron-based amination system in as ulfoxide imidation reaction to form unprotected sulfoximines. [16] However,t he reactivity of the lower oxidation sulfur analogue like thiols [88] has remained unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier OECD research 21 already highlighted the changing role that large SOEs play in the international market place. The expansion of SOEs in foreign markets is not always restricted to purely commercial considerations.…”
Section: Cross-border Investmentsmentioning
confidence: 99%
“…Togni and Carreira [8h] as well as Ritter [8g] reported that N ‐OTf pyridine as pyridine radical cation could be used for the construction of C−N bonds in 2019. Recently, in an iron‐catalyzed process, meta‐C−H aminated products were achieved with HOSA (hydroxylamine‐ O ‐sulfonic acid) and picolinates as directing group by Falck; [10f] and a Ti‐catalyzed arene C−H amination was reported with simple NH 2 OH ⋅ HCl by Sanford [10g] . Besides, commercially available HOSA and DPH ( O ‐(2,4‐dinitrophenyl)hydroxylamine) were used for aziridinations of olefins with rhodium as catalyst, which was reported by Kürti and Falck [11] .…”
Section: Introductionmentioning
confidence: 99%